Marketing of hospital services by non-gorvernmental organisations - Vrinda Sreenivasan (Department of Rural Marketing Management, College of Co-operation and Banking, 1995)
The study entitled ‘Marketing of Hospital Services by Non – Governmental Organisations’ was undertaken to examine the marketing practices adopted by the non-governmental organizations rendering hospital services and to assess its effectiveness, and to study the attitude of patients, doctors and paramedicals towards the present hospital services.